A Study on the Potential of Natural Liquid Electrolytes from Lime Peel, Starfruit, and White Vinegar for Renewable Energy Bio-Batteries - Suryadhi Firdaus; Rusdianasari Rusdianasari; Tresna Dewi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The purpose of this study is to evaluate the performance of bio-batteries utilizing natural liquid electrolytes made from white vinegar, lime peel, and star fruit. The bio-battery uses copper (Cu) and zinc (Zn) electrodes to function according to galvanic cell principles. With an overall average efficiency of 50% in all test intervals (5, 10, 15, and 30 minutes), composition 47, which consists of 35 ml of lime peel liquid extract, 35 ml of starfruit liquid extract, and 10 ml of white vinegar liquid, is the ideal composition for the bio battery liquid electrolyte. The results show that the electrical power generated ranges from 0.0007 to 0.0008 W, with an average acidity level (pH) of 2.15 and an average conductivity of 3.85 µs/cm. Ion mobility and electrochemical reactions were significantly affected by the electrolyte's characteristics, particularly its high conductivity and low pH. While additional tweaking is required to increase the bio battery's efficiency and electrical power production. This study demonstrates the promise of organic waste as an eco-friendly alternative energy source. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 13: Climate Action